The effect of esmolol on corrected-QT interval, corrected-QT interval dispersion changes seen during anesthesia induction in hypertensive patients taking an angiotensin-converting enzyme inhibitor - Çeker,Zahit (2015)
BACKGROUND AND OBJECTIVES: The importance of minimizing the exaggerated sympatho-adrenergic responses and QT interval and QT interval dispersion changes that may develop due to laryngoscopy and tracheal intubation during anesthesia induction in the hypertensive patients is clear. Esmolol decreases the hemodynamic response to laryngoscopy and intubation. However, the effect of esmolol in decreasing the prolonged QT interval and QT interval dispersion as induced by laryngoscopy and intubation is controversial. We investigated the effect of esmolol on the hemodynamic, and corrected-QT interval and corrected-QT interval dispersion changes seen during anesthesia induction in hypertensive patients using angiotensin converting enzyme inhibitors. METHODS: 60 ASA I-II patients, with essential hypertension using angiotensin converting enzyme inhibitors were included in the study. The esmolol group received esmolol at a bolus dose of 500 mcg/kg followed by a 100 mcg/kg/min infusion which continued until the 4th min after intubation. The control group received 0.9% saline similar to the esmolol group. The mean blood pressure, heart rate values and the electrocardiogram records were obtained as baseline values before the anesthesia, 5 min after esmolol and saline administration, 3 min after the induction and 30 s, 2 min and 4 min after intubation. RESULTS: The corrected-QT interval was shorter in the esmolol group (p = 0.012), the corrected-QT interval dispersion interval was longer in the control group (p = 0.034) and the mean heart rate was higher in the control group (p = 0.022) 30 s after intubation. The risk of arrhythmia frequency was higher in the control group in the 4-min period following intubation (p = 0.038). CONCLUSION: Endotracheal intubation was found to prolong corrected-QT interval and corrected-QT interval dispersion, and increase the heart rate during anesthesia induction with propofol in hypertensive patients using angiotensin converting enzyme inhibitors. These effects were prevented with esmolol (500 mcg/kg bolus, followed by 100 mcg/kg/min infusion). During induction, the blood pressure tends to decrease with esmolol where care is needed.